Development, roll-out and implementation of an antimicrobial resistance training curriculum harmonizes delivery of in-service training to healthcare workers in Kenya - Njeru, Josiah; Odero, Joshua; Chebore, Sheilla; Ndung’u, Mungai; Tanui, Emmanuel; Wesangula, Evelyn; Ndanyi, Romona; Githii, Susan; Gunturu, Revathi; Mwangi, Willy; Mutonga, David; Dahourou, Anicet; et al. (Frontiers in Microbiology, 2023)
Background Antimicrobial resistance (AMR) is an increasingly severe threat to global public health that requires action across different sectors. Selection of appropriate antimicrobials is an urgent challenge due to the emergence of drug resistance. In 2017, Kenya developed an AMR policy and National Action Plan to drive prevention and containment of AMR. A priority activity under AMR surveillance strategic objective was to develop a national AMR training curriculum for in-service healthcare workers. In this paper we discuss the development, gains achieved through implementation across the country and lessons learned. Methods An initial stakeholders’ forum was convened to brainstorm on the process for developing the curriculum and some issues deliberated upon include the design approach, development roadmap, curriculum outline and scope, delivery, and evaluation methodologies. A team of subject matter experts (SMEs), drawn from the project and government ministries, compiled the initial draft of the curriculum and later the training materials. A series of other stakeholders’ meetings were convened to review these materials. The National Antimicrobial Stewardship Interagency Committee (NASIC) of the MOH in Kenya identified a team of experts from academia, research, and government to work with the SMEs in reviewing and providing valuable inputs to the curriculum. Additionally, principles of adult learning and a One Health approach for development were considered as AMR has drivers and impacts across sectors. A validation workshop was held to finalize the documents with a formal launch conducted during the World Antibiotics Awareness Week of 2020. Results A multisectoral AMR surveillance training curriculum and facilitator and trainee manuals were developed and endorsed by MOH and Ministry of Agriculture, Livestock, Fisheries and Cooperatives within one year. Over 500 healthcare workers in 19 counties were trained, with overwhelming adoption by other stakeholders in Kenya and beyond. Conclusion This curriculum was developed to standardize training for AMR detection and surveillance. The central role played by the MOH ensured expeditious development and roll-out of this curriculum. The in-service curriculum, now available on an e-learning platform, provides a ready opportunity to build capacity of healthcare professionals. Additional resources are needed to scale these efforts to reach all healthcare workers.